The Effect of Financial Literacy on The Income of Vannamei Shrimp Farmers in West Aceh Regency (Case Study of Samatiga District) - Safitri, Irda; Ansari, Leli Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the effect of financial literacy on the income of Vannamei shrimp farmers in West Aceh Regency with a case study in Samatiga District. This research is quantitative, described qualitatively. The research variables consist of financial literacy as the independent variable and income as the dependent variable. The research method uses primary data obtained from a questionnaire, with a population and sample size of 16 respondents, specifically Vannamei shrimp farmers, with a sampling technique using total sampling. Based on the research results, it shows that financial literacy has a positive effect on the income of Vannamei shrimp farmers, as evidenced by an average income of IDR 2,144,278,619 and an average profit of IDR 46,292,957 per production (harvest). However, these profits do not meet expectations, as most Vannamei shrimp farmers lack financial literacy, resulting in inefficient and ineffective income allocation. This issue is rooted in low education levels, indicating a need for financial literacy socialization and training.